2017
DOI: 10.1007/s00394-017-1437-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8-weeks prebiotics/probiotics supplementation on alcohol metabolism and blood biomarkers of healthy adults: a pilot study

Abstract: Consumption of probiotics appears to alter faecal counts of supplemental bacterial strains in otherwise healthy individuals. However, translation to any possible beneficial impact on alcohol metabolism remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Seven studies also reported changes in fasting blood glucose (FBG) and insulin levels. Of these, four reported no significant changes in FBG or insulin levels (55,64,71,72), two reported reduction in FBG and insulin level (62,68) and one reported an increase in FBG after probiotics supplementation in healthy adults (65). Similar to BMI, the evidence is inconclusive for the beneficial effect of probiotics on FBG and insulin level in healthy adults.…”
Section: Immune System Responsementioning
confidence: 97%
See 3 more Smart Citations
“…Seven studies also reported changes in fasting blood glucose (FBG) and insulin levels. Of these, four reported no significant changes in FBG or insulin levels (55,64,71,72), two reported reduction in FBG and insulin level (62,68) and one reported an increase in FBG after probiotics supplementation in healthy adults (65). Similar to BMI, the evidence is inconclusive for the beneficial effect of probiotics on FBG and insulin level in healthy adults.…”
Section: Immune System Responsementioning
confidence: 97%
“…However, these findings are in contrast with the results of several other studies indicating that probiotic supplementation had no influence on the incidence (47,48,50) or severity (47,48) Changes in BMI were reported in six studies (Table 3). Of these four reported no significant changes (18,55,67,71) and one reported a significant increase in BMI after probiotic supplementation (65). One of the studies assessed the BMI increase after four weeks of highfat diet and reported a lower increase in BMI in the probiotic group compared to placebo (72).…”
Section: Immune System Responsementioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence for the health benefits of probiotics, including enhancement of the immune response (Khalesi et al, 2018), a protective role against allergy (Sharma and Im, 2018;Szari and Quinn, 2019), removal of chemical contaminants and ability to reduce the toxicity of contaminants (Feng et al, 2018;Wochner et al, 2018;Wang et al, 2019), improving intestinal health by modulating the number and diversity of beneficial gut microbiota, and reducing symptoms associated with various gastrointestinal disorders (Ferrario et al, 2014;Ford et al, 2014;Feng et al, 2018;Irwin et al, 2018;Vasquez et al, 2019), hepatoprotective effects (Meng et al, 2018), cardiovascular disease prevention by improving blood cholesterol levels and blood lipid profile, reducing blood pressure and hypertension (Guo et al, 2011;Khalesi et al, 2014;Sun and Buys, 2015;Vasquez et al, 2019), improving blood glucose tolerance and diabetes control (Sun and Buys, 2016;Plows et al, 2019), improved mental health (Inserra et al, 2018;Bruce-Keller et al, 2018;Dutta et al, 2019), and cancer prevention (Nazir et al, 2018;Scott et al, 2018;Ma et al, 2019). However, in order to improve the probability of these beneficial effects, probiotic candidate strains should be submitted to selection assays, which can be crucial to promulgate the therapeutic effect in the host.…”
Section: Benefits Of Probiotic Organismsmentioning
confidence: 99%